Pengaruh Media Pembelajaran dan Penguasaan Struktur Kalimat terhadap Hasil Belajar Menulis Bahasa Inggris Siswa SMP Swasta Kecamatan Tapos Depok - Megawati M (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2016)
The research has done of the seventh grade students at SMP Swasta Depok by using the experimental research method. The total sample of this research followed by 60 students. The writer applied the purpose sampling to determine the sample. The technique of collecting data power point teaching media used likert scale or questioners, sentence structure mastery and the writing skill was acquired from the test. The research of instrument has tested and tried by the validity and the reliability test used the programs of SPSS (statistic program social science) The data was analysed by using 2 way analysis of variances (ANOVA). Before doing the analysis, the data normality was tested by using Kolmogorov-Smirnov test to see if the population where the sample was taken had normal distribution. The next analysis is to test the data homogeneity by using levenu’s test, to see if the population was derived from homogenous population. The result of the research concluded: 1). Using power point teaching media gave the significant effect to the student’s writing skill. Test result obtained that p-value for category learning media is 0.000 (< 0.05), then the conclusion is that there is significant difference towards student’s writing skill in the application conventional teaching media. 2). Sentence structure mastery gave the significant effect to the student’s writing skill. Test result obtained that p-value for sentence structure mastery 0.000 (<0.05). 3). There is interaction influence between using media learning and sentence structure mastery towards student’s writing skill. Test result retrieved that p-value for category of teaching media and sentence structure mastery is 0.001 (< 0.05).